O aprendizado da Filosofia do Direito e a experiência na Pontifícia Universidade Católica de São Paulo (PUC-SP) - Gomes, Yara Alves (2016)
The Law Course is responsible to train professionals capable of in the exercise of their functions to be able to achieve the effectiveness of justice. However, in order to obtain the properly preparation during the graduation, it's necessary for the legal courses to be worried about the humanitarian qualifications of the graduating students, because the education can't be limited to the transferring of dogmatic. In face of the concern about critical qualification, zetetic subjects are inserted on the curriculum of law school and, in this specific study, we intend to analyze the expectations the Legal Academy has about the Philosophy Of Law, the learning process of the discipline, their presence in Law School’s curriculum, and their taught at Pontifical Catholic University of São Paulo